The Effect of Financial Literacy and Self-Control on the Financial Behavior of Economic Education Students of FKIP Universitas Riau - Yulia Nanda Vika; Gusnardi Gusnardi; M. Yogi Riyantama Isjoni (CV. Rayyan Dwi Bharata, 2023)
This study aims to determine the effect of financial literacy and self-control on the financial behavior of Economics Education FKIP University of Riau students. The population in this study were active students of the Bachelor of Economics Study Program, Faculty of Teacher Training and Education, University of Riau who lived in boarding houses. The sample in this study amounted to 123 students with a sampling technique using saturated sampling technique. The data collection method used questionnaires which were distributed directly and the data collected was then tabulated and analyzed using multiple linear regression. Hypothesis testing is done by F test and t test. Based on the results of the study stated that financial literacy and self-control have a positive and significant effect on financial behavior both simultaneously and partially. Therefore, if students have good financial literacy and controlled self-control, the financial behavior of students who live in boarding houses will also improve.